Comparison of test-day and lactation models of sire evaluation in Murrah buffalo - KUMAR, VIJAY; CHAKRAVARTY, A K; PATIL, C S; VALSALAN, JAMUNA; MAHAJAN, ATUL; SHIVAHRE, PUSHP RAJ (The Indian Journal of Animal Sciences, 2014)
The aim of the study was to investigate efficiency of test-day model (TDM) compared to lactation model (LM) for genetic evaluation of Murrah buffalo bulls. Use of TDM instead of LM is of more interest in genetic evaluation because of variability of lactation days in dairy animals. Data pertaining to first lactation monthly test-day milk yield (FLMTDMY) and first lactation 305-days or less milk yield (FL305DMY) of 1,105 Murrah buffalo during 1993 to 2010 were collected and adjusted against significant environmental influences. It was found that test-day 6 milk yield (FLMTD6MY) had the highest genetic and phenotypic correlation with FL305DMY. An attempt is being made in the present investigation to compare the estimated breeding values (EBVs) of Murrah bulls through best linear unbiased prediction for FL305DMY and FLMTD6MY. The rank correlations between 2 traits were highly statistically significant indicating that FLMTD6MY is equally effective to discriminate amongst sires.